A Forty-One Year Old Man Died of Hepatocellular Carcinoma from Hepatitis B - Kong, MD, Xuejun (North American Journal of Medicine and Science, 2008)
Hepatocellular carcinoma (HCC) is a primary liver malignancy, the global incidence is about 15 cases per incidence of HCC 137,000 new cases.1 The most important risk factor is viral hepatitis, especially hepatitis B.2-3 Among Chinese population, 15-20% is described as HBV carriers (hepatitis B surface antigen positive). The relative risk of HCC among Hepatitis B carriers is 223 times that of non-carriers. These chronic carriers are usually not symptomatic and have normal liver function. Despite this, they are at risk of developing Hepatocellular carcinoma without signs of cirrhosis, active or advanced hepatitis. Unfortunately, the diagnosis is usually late4-5 and the prognosis is generally poor, as the case described above.